2015
DOI: 10.1523/jneurosci.0006-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Oligomers Disrupt Blood–CSF Barrier Integrity by Activating Matrix Metalloproteinases

Abstract: The blood-CSF barrier (BCSFB) consists of a monolayer of choroid plexus epithelial (CPE) cells that maintain CNS homeostasis by producing CSF and restricting the passage of undesirable molecules and pathogens into the brain. Alzheimer's disease is the most common progressive neurodegenerative disorder and is characterized by the presence of amyloid ␤ (A␤) plaques and neurofibrillary tangles in the brain. Recent research shows that Alzheimer's disease is associated with morphological changes in CPE cells and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
183
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(197 citation statements)
references
References 85 publications
8
183
4
2
Order By: Relevance
“…Under healthy conditions, however, the blood-CSF barrier (BCSFB) formed by the choroid plexus epithelial cells restricts immune-cell entry into the CSF and the brain parenchyma (Baruch and Schwartz, 2013; Engelhardt et al, 2001; Hasegawa-Ishii et al, 2013). AD patients exhibit major alterations in choroid plexus structure and morphology, as well as in epithelial cell function, attributable mainly to the increase in toxic Aβ peptides (Brkic et al, 2015; Johanson et al, 2004; Vargas et al, 2010). In addition, the ability of epithelial cells to express the transporters that participate in Aβ efflux, as well as to secrete Aβ-scavenging proteins into the CSF and their corresponding receptors, decreases with age and is compromised in different in-vitro and in-vivo models of AD (Antequera et al, 2009; Crossgrove et al, 2005; Zlokovic et al, 1996).…”
Section: Choroid Plexus In Admentioning
confidence: 99%
“…Under healthy conditions, however, the blood-CSF barrier (BCSFB) formed by the choroid plexus epithelial cells restricts immune-cell entry into the CSF and the brain parenchyma (Baruch and Schwartz, 2013; Engelhardt et al, 2001; Hasegawa-Ishii et al, 2013). AD patients exhibit major alterations in choroid plexus structure and morphology, as well as in epithelial cell function, attributable mainly to the increase in toxic Aβ peptides (Brkic et al, 2015; Johanson et al, 2004; Vargas et al, 2010). In addition, the ability of epithelial cells to express the transporters that participate in Aβ efflux, as well as to secrete Aβ-scavenging proteins into the CSF and their corresponding receptors, decreases with age and is compromised in different in-vitro and in-vivo models of AD (Antequera et al, 2009; Crossgrove et al, 2005; Zlokovic et al, 1996).…”
Section: Choroid Plexus In Admentioning
confidence: 99%
“…Several reports describe that matrix metalloproteinases (MMPs), i.e., Zn 2+ -dependent endopeptidases that cleave both matrix and non-matrix proteins, are able to degrade basal lamina components and tight junction proteins at the blood–brain barrier (BBB), blood–cerebrospinal fluid barrier (BCSFB) and blood–spinal cord barrier (BSCB), thereby contributing to blood–central nervous system (CNS) barrier disruption and neuroinflammation [11,12,13,14,15,16,17,18,19]. Of note, it is known that the endothelial cells of the BBB/BSCB and the choroid plexus epithelial cells (CPE) that form the BCSFB show similarities with, respectively, the endothelial cells of the inner BRB and the RPE cells of the outer BRB [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, MMP expression is known to be upregulated by cytokines but also by the bacterial endotoxin LPS. In addition, increased MMP-3 levels have been reported during neuroinflammatory processes [11,14,21,22,23,24,25,26]. Indeed, the MMP-3 gene ( Mmp3 ) promoter contains binding sites for activator protein 1 (AP-1) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), which can both be activated by various inflammatory cytokines [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…This study further demonstrated that a combination of mobilized direct AD biomarkers from the brain into blood [10] and an analysis of signature PC levels in the pramlintide challenge test may be a valuable diagnostic test for AD (Figure 5). The existence of BBB and blood-CSF barrier (BCSFB) prevent brain-originating AD biomarkers in the blood from accurately reflecting brain pathology [24, 25] and cause challenges to develop blood diagnostic tests for AD. For example, although plasma Aβ levels are significantly different between AD and controls when a large sample size is used [26, 27], the sensitivity and specificity of these differences are too low to be useful as AD diagnostics [28] [29, 30].…”
Section: Discussionmentioning
confidence: 99%